Behavioral responses to inheritance taxation: A review of the empirical literature - Margit Schratzenstaller (Austrian Institute of Economic Research (WIFO), 2023)
Wealth inequality and concentration, together with the search for options to secure long-term sufficiency of tax systems in face of ageing societies, have recently moved the taxation of inheritances into the spotlight. The question if and to what extent behavioral responses by bequeathers may undermine the revenue potential of inheritance taxes is central for policy design. This survey of the empirical literature finds an overall moderate impact of inheritance taxation on wealth accumulation and residential choice. This holds true also for the impact of inheritance taxes on tax planning and avoidance in general as well as inter vivos transfers in particular. Tax planning, avoidance and evasion responses are more pronounced than real responses. Behavioral responses to an inheritance tax are smaller compared to a recurrent net wealth tax. Therefore, policymakers aiming at the minimization of (revenue-reducing) behavioral responses should prefer an inheritance tax over a recurrent net wealth tax. Furthermore, the containment of (illegal) tax avoidance should be a priority for policymakers in order to secure legitimacy of and public support for inheritance taxation, but also to ensure that inheritance taxes are an efficient tool to reduce inequality, considering that avoidance and evasion are highly concentrated among the rich.
Keywords: D9; H24; H26; H3; 330; Inheritance taxation; Wealth taxation; Behavioural responses; Tax elasticities; Tax avoidance